Kemampuan dan kepemimpinan transformasional dalam mempengaruhi kinerja karyawan melalui komitmen organisasional dan motivasi - Indro Kirono; Sukaris Sukaris; Abi Hanif Dzulquarnain; Abdurrahman Faris Indriya Himawan; Anita Akhiruddin (Journal of Business & Banking, 2021)
This study aims to determine the relationship between employee ability and leadership through commitment and motivation towards the employees’ performance at PT. X that are engaged in logistics. The results showed that the model placing organizational com- mitment as a construct proved to be better than the one measuring organizational com- mitment as a multi-construct affective commitment, continuous commitment, and nor- mative commitment. It also showed that between commitment dimensions are highly correlated with each other and therefore it leads to residues correlate with each other’s. Based on the path coefﬁcient test on the modiﬁcation model, namely placing commitment as a construct, it indicated as follows: Transformational leadership has a signiﬁcant positive inﬂuence on organizational commitment. Transformational leadership has a signiﬁcant effect on employee work motivation, organizational commitment proved to have a signiﬁcant positive effect on employee work motivation, work motivation proved to have a signiﬁcant positive effect on employee performance. The employees’ ability proved to have a signiﬁcant positive effect on employee performance. The research implication of this study is a form of human resources development in the company, especially in terms of performance by manipulating its internal leadership and commitment. In the future this can be one way to develop its internal HR.